Case Report: Insulin hypersensitivity in youth with type 1 diabetes - Alkhatib, Einas H.; Grundman, Jody B.; Adamusiak, Anna M.; Bellin, Melena D.; Brooks, Joel P.; Buckley, Kevin S.; Janssen, Erin M.; Kitcharoensakkul, Maleewan; McNerney, Kyle P.; Pfeifer, Thea L.; Polk, Brooke I.; Marks, Brynn E. (Frontiers in Endocrinology, 2023)
Objective: Immediate type I, type III, and delayed type IV hypersensitivity reactions to insulin are rare, but potentially serious complications of exogenous insulin administration required for the treatment of type 1 diabetes (T1D). Methods: We present four cases of insulin hypersensitivity reactions occurring in youth with T1D and a literature review of this topic. Results: Insulin hypersensitivity reactions included types I, III, and IV with presentations ranging from localized urticaria, erythematous nodules, and eczematous plaques to anaphylaxis with respiratory distress. Reactions occurred in youth with newly diagnosed T1D and in those with long-standing T1D who were using both injection and insulin pump therapy. Multidisciplinary care involving pediatric endocrinology and allergy/immunology utilizing trials of many adjunct therapies yielded minimal improvement. Despite the use of various treatments, including antihistamines, topical therapies, immunosuppressant medications, desensitization trials, and intravenous immune globulin, cutaneous reactions, elevated hemoglobin A1c levels, and negative effects on quality of life remain persistent challenges. One patient became one of the youngest pancreas transplant recipients in the world at age 12 years due to uncontrollable symptoms and intolerable adverse effects of attempted therapies.Although rare, insulin hypersensitivity reactions negatively affect glycemic control and quality of life. These cases demonstrate the varying severity and presentation of insulin hypersensitivity reactions along with the limited success of various treatment approaches. Given the life-sustaining nature of insulin therapy, further studies are needed to better understand the underlying pathophysiology of insulin hypersensitivity and to develop targeted treatment approaches. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership. References should not be cited in the abstract. Leave the Abstract empty if your article does not require oneplease see the "Article types" on every Frontiers journal page for full details.